Norovirus Infection and Acquired Immunity in 8 Countries: Results From the MAL-ED Study. (24th March 2016) - Rouhani, Saba; Peñataro Yori, Pablo; Paredes Olortegui, Maribel; Siguas Salas, Mery; Rengifo Trigoso, Dixner; Mondal, Dinesh; Bodhidatta, Ladaporn; Platts-Mills, James; Samie, Amidou; Kabir, Furqan; Lima, Aldo; Babji, Sudhir; et al.
Abstract : This longitudinal, multisite study reports a high prevalence of norovirus infection and norovirus-positive diarrhea and describes patterns of age acquisition, disease severity, genogroup-specific immunity, and relationships between norovirus and undernutrition in the first 2 years of life. Abstract: Background. Norovirus is an important cause of childhood diarrhea. We present data from a longitudinal, multicountry study describing norovirus epidemiology during the first 2 years of life. Methods. A birth cohort of 1457 children across 8 countries contributed 7077 diarrheal stools for norovirus testing. A subset of 199 children contributed additional asymptomatic samples (2307) and diarrheal stools (770), which were used to derive incidence rates and evaluate evidence for acquired immunity. Results. Across sites, 89% of children experienced at least 1 norovirus infection before 24 months, and 22.7% of all diarrheal stools were norovirus positive. Severity of norovirus-positive diarrhea was comparable to other enteropathogens, with the exception of rotavirus. Incidence of genogroup II (GII) infection was higher than genogroup I and peaked at 6–11 months across sites. Undernutrition was a risk factor for symptomatic norovirus infection, with an increase in 1 standard deviation of length-for-age z score associated with a 17% reduction (odds ratio, 0.83 [95% confidence interval, .72–.97]; P = .011) in the odds of experiencing diarrhea when norovirus was present, after accounting for genogroup, rotavirus vaccine, and age. Evidence of acquired immunity was observed among GII infections only: Children with prior GII infection were found to have a 27% reduction in the hazard of subsequent infection (hazard ratio, 0.727; P = .010). Conclusions. The high prevalence of norovirus across 8 sites in highly variable epidemiologic settings and demonstration of protective immunity for GII infections provide support for investment in vaccine development.